Rubella-specific IgM detected by an antibody capture assay/ELISA technique. - Kurtz, J B (1981)
A sensitive method for detecting rubella IgM antibody, the first step of which is the attachment of the serum IgM to a solid phase, is described. Specific IgM antibody was found in all 52 people with acquired rubella in the early convalescent period, in all 38 infants with congenital rubella examined in the first seven months of life, and in 23 of 26 people immunised one to four months before testing. Twenty-four of 44 rheumatoid factor-positive sera, however, gave false-positive readings. In routine use the test was economical of both reagents and time.